Similarities and differences in gene expression profiles of BRCA1 methylated and mutated epithelial ovarian cancers - Sahnane, Nora; Libera, Laura; Facchi, Sofia; Carnevali, Ileana; Ronchi, Susanna; Albeni, Chiara; Cromi, Antonella; Casarin, Jvan; Sessa, Fausto; Tibiletti, Maria Grazia (Frontiers in Oncology, 2023)
Introduction BRCA1 methylated (BRCA1met) epithelial ovarian cancer (EOC) is a recently defined and not well-investigated subset of neoplasms. To date, no studies have focused on the transcriptional profiles of BRCA1met cases, and, as a matter of fact, we still do not know if this subset of EOCs is similar, and to what extent, to BRCA1 mutated (BRCA1mut) cases. Methods We compared a group of 17 BRCA1met cases against 10 BRCA1mut cases using a subset of carefully selected 17 BRCAwt EOCs as a control group. Results First, BRCA1met cases showed a downregulation of the relative transcript, while this association was not observed for BRCA1mut EOCs. The BRCA1met group exhibited a general upregulation of homologous recombination (HR)-related genes, as well as BRCA1mut. Overall, BRCA1met had a different gene expression profile, characterized by diffuse downregulation, whereas BRCA1mut showed a general upregulation (p < 0.0001). Both BRCA1-defective groups showed a slightly activated immune response mediated by interferon (IFN) gamma pathways. Discussion In conclusion, even if the expression profile of many genes related to DNA damage and repair system is shared between BRCA1mut and BRCA1met EOCs supporting that BRCA1met EOCs may benefit from PARPi therapies, our data demonstrate that BRCA1mut and BRCA1met EOCs show different expression profiles, suggesting a different mechanism of carcinogenesis that can be reflected in different responses to therapies and disease recovery.